Review on genetic transformation of rice / Nur Amalina Ghazali - Ghazali, Nur Amalina (Faculty of Plantation and Agrotechnology, 2019)
Rice or its scientific name, Oryza sativa L. is one of the world’s valuable crops. It is cultivated worldwide on 8.2 million hectares in 58 countries annually. Rice is a dietary staple food and one of the most important cereal crops, especially for people in Asia. A switch in production and consumption patterns would improve food security where food grains are scarce, and provide more health beneficial food components, may prevent some diseases and ease the burden on the earth. Modern applications of agricultural biotechnology involves the development of gene transfer methods for the genetic transformation to increase number of important crops in daily life especially rice. The establishment of an efficient genetic transformation protocol for rice is important in improvement of traits. Despite a variety of available DNA delivery methods, Agrobacterium and biolistic mediated transformation remain two predominantly applied approaches. Most of the studies suggested that the transformation efficiency of the indica rice varieties is unsatisfactory in comparison to japonica cultivars as majority of the indica rice varieties are recalcitrant to in vitro responses. For efficient plant transformation, the selection of actively growing regenerable calli and the optimization of the culture conditions for the co-cultivation of rice calli with Agrobacterium are the most important factors. Acetosyringone was found as an essential key factor in achieving the rice transformation. Maximum rice transformation efficiency was achieved with the presence of acetosyringone at 100 μM. In conclusion, the factors that affecting the transformation efficiency of rice have been determined in this review.